How to be a holist who rejects the biopsychosocial model - O'Leary, Diane (2021)
After nearly fifty years of mea culpas and explanatory additions, the biopsychosocial model is no closer to a life of its own. Bolton and Gillett give it a strong philosophical boost in The Biopsychosocial Model of Health and Disease, but they overlook the model"s deeply inconsistent position on dualism. Moreover, because metaphysical confusion has clinical ramifications in medicine, their solution sidesteps the model"s most pressing clinical faults. But the news is not all bad. We can maintain the merits of holism as we let go of the inchoate bag of platitudes that is the biopsychosocial model. We can accept holism as the metaphysical open door that it is, just a willingness to recognize the reality of human experience, and the sense in which that reality forces medicine to address biological, psychological, and social aspects of health. This allows us to finally characterize Engel"s driving idea in accurate philosophical terms, as acceptance of (phenomenal) consciousness in the context of medical science. This will not entirely pin down medicine"s stance on dualism, but it will position it clearly enough to readily improve patient care.
Nakon gotovo pedeset godina mea culpas i objašnjavajućih dodataka, biopsihosocijalni model nije ništa bliži vlastitom životu. Bolton i Gillett daju mu snažan filozofski poticaj u Biopsihosocijalnom modelu zdravlja i bolesti, ali zanemaruju duboko nedosljedan stav koji model ima prema dualizmu. Štoviše, budući da metafizička zbrka ima kliničke posljedice u medicini, njihovo rješenje zaobilazi najhitnije kliničke greške modela. Ali nije sve tako crno. Možemo zadržati dobre strane holizma istovremeno napuštajući floskule koje pretpsotavlja biopsihosocijalni model. Možemo prihvatiti holizam kao metafizički otvorena vrata koja on jest, samo spremnost da se prepozna stvarnost ljudskog iskustva i smisao u kojem ta stvarnost tjera medicinu da se pozabavi biološkim, psihološkim i društvenim aspektima zdravlja. To nam omogućuje da konačno okarakteriziramo Engelovu pokretačku ideju u točnim filozofskim terminima, kao prihvaćanje (fenomenalne) svijesti u kontekstu medicinske znanosti. To neće u potpunosti odrediti stav medicine prema dualizmu, ali će ga postaviti dovoljno jasno da se lako poboljša skrb za pacijente.
Bibliografija: str. 19-20.
Abstract ; Sažetak.
Keywords: Biopsihosocijalni model -- Holizam -- Dualizam -- Filozofija medicine -- Psihosomatska medicina